(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A Surrogacy is the medical term used for the process when another women carries and gives birth to a baby for the couple who want to have a child and is really appropriate to opt in these cases where the medical conditions of the spouse makes it impossible or dangerous to get pregnant and to give birth. Before the scientific technological development of practice of ‘surrogacy’ an adoption was in practice for those couples who cannot have their own naturally born child due to infertility or any other complex medical reasons. But after the origin and development of practice of ‘surrogacy’ an adoption is an underutilized option that can not only give happiness to a childless couple but also provide a future for an orphan child. There are many pros and cons legality and legalizing surrogacy debatable in India. The debate of legal issues was began when in 2008, a Japanese doctor couple commissioned a baby in a small town in Gujarat. The surrogate mother brought forth a solid baby young lady. By then the couple had isolated and the baby was both parentless and stateless, got between the legal frameworks of two nations. The youngster is currently in her grandmother’s guardianship in Japan however has gotten citizenship, as surrogacy isn’t legal in Japan. Another kind of legal issues rose in year 2012, when an Australian couple who had twins by surrogacy, subjectively dismissed one and brought home at other. Such episodes are cited here to feature the all out negligence for the privileges of the surrogate mother and kid and have brought about various open intrigue prosecutions in the Supreme Court to control commercial surrogacy. The 228th Report of the Law Commission of India likewise suggested denying commercial surrogacy and permitting moral charitable surrogacy to poor resident by ordering a reasonable enactment. The surrogacy (Regulation) Bill,2019 proposes to control surrogacy in India by allowing it as a possibility for couples who can’t normally have youngsters, have an absence of other helped conceptive innovation choices, are quick to have a natural kid, and can locate a surrogate mother among their family members. In India Article 21 of the constitution of India, judgments of the Supreme court ,Judicial Activism Reproductive Bill, 2010 and other legal provisions cannot prevent the practice of commercialize surrogacy. This kind of practice will definitely mar the future of the new born baby and the surrogate mother’s health which is humiliating and inhuman too. The utmost step which is at present required to stop this mal practice is to make people aware of their social responsibilities and about the guidelines of surrogacy legal provisions, arrangements or agreements so that the rights of surrogate mother as well as of child can be protected. To attain a mother would still considered as a gift to a woman but few are taking advantages of this at the cost of violation of rules of nature.